2018
DOI: 10.32394/pe.72.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Positive health behaviours Polish and Ukrainian medical students in the context of chronic diseases

Abstract: INTRODUCTION. Medical studies and practicing the medical professions involve considerable psychological distress. Health risks associated with distress may be greater in people with health problems, especially in the case of insufficient self-care for health. AIM. Investigating the frequency of positive health behaviours and avoiding risky behaviours among students of medical faculties with and without chronic diseases. MATERIAL AND METHODS. 796 students of the first years of the faculties of general medicine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Most of the programs we have found were designed to lower anxiety levels [37], and with good results. In this line, music therapy helps to boost mood and is commonly used in nursing intervention programs with good results [38]. Other studies aimed at the motivation and self-management of the chronic patient have confirmed that attention to and support of these patients are the keys to success [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the programs we have found were designed to lower anxiety levels [37], and with good results. In this line, music therapy helps to boost mood and is commonly used in nursing intervention programs with good results [38]. Other studies aimed at the motivation and self-management of the chronic patient have confirmed that attention to and support of these patients are the keys to success [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of health-related behaviours of students of medical faculties from Poland and Ukraine show that Polish students rated health higher, more often consumed regular meals, vegetables and reduced animal fats, as well as took care of oral hygiene and cared about road safety. In the case of health practices -taking care of rest and adequate number of hours of sleep (6-7 per day), a statistically significant difference was noted in favour of Ukrainian students (Woynarowska-Sołdan, Yezhova, Sytnyk, & Węziak-Białowolska, 2018). According to the authors of the study, these differences were affected by, inter alia, a more difficult socio-economic situation of Ukrainian students.…”
Section: Discussionmentioning
confidence: 80%
“…"the desire of a person to improve the results of their activities". This need makes students concentrate more on their studies and at the same time increases their social activity and positively affects their health [20].…”
Section: S Learning Activitiesmentioning
confidence: 99%